The Egyptian Financial Supervisory Authority (EFSA) Resolution of EFSA's Board of Directors No. 46 of the Year 2017, dated 19/4/2017, on Amending EFSA's Board Resolution No. 72 of the Year 2013, Regarding the Regulations and Controls Governing the Factoring Activity = الهيئة العامة للرقابة المالية قرار مجلس إدارة الهئية رقم 46 لسنة 2017 بتاريخ 19/4/2017 بتعديل قرار مجلس إدارة الهيئة رقم 72 لسنة 2013 بشأن الضوابط التنظيمية والرقابية لنشاط التخصيم - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic